(untitled) (Revista Rupturas, 2025)
The Brazilian structural condition is marked by inequality, which is worsened by the persistence and deepening of informal work and income instability of the most vulnerable groups. It is from the perspective of trying to overcome poverty and extreme poverty that proposals for basic income and programs such as Bolsa Família and Auxílio Brasil are debated. This study is the result of documentary and bibliographical research, carried out in 2024, with the aim of reflecting on income transfer in Brazil. The research findings indicate that the PBF, despite its relevance in reducing poverty, prevented the basic income proposal from being adopted as a federal policy and, therefore, valid for the entire country.